Data Science: a description of the first data science undergraduate courses in Brazilian universities - Ara, Anderson (2023)
Due to the increasing volume of data, the urgency to look for suitably qualified data scientists has grown. Thus, Brazilian Higher Education Institutions (HEIs) have tried to answer this demand. In this scenario, the objective of this paper is to perform a characterization of undergraduate courses in Data Science. Thus, we aim to answer questions such as: have the courses been offered in the vast majority by public or private universities? When did they start being offered? Are they usually ODL (Online Distance Learning or in-person? Are they the technological type or baccalaureate? What groups of disciplines most make up the curriculum? In which regions of the country are they concentrated? How is the offer of vacancies and what is the profile of admissions in bachelor and technological courses? For this, the e-MEC databases and the 2021 Higher Education Census were combined, and it was decided to explore and visualize data using the MCA technique. Among the results, it is observed that there is a certain balance between the in-person and online learning modalities, in addition to the fact that most of the courses are of the technological type and are usually offered by private HEIs. Regarding the regions, a significant number of in-person undergraduate courses are concentrated in the Southeast region of Brazil.